Barium borosilicate glass coatings based on biomass for steel surfaces: Use of rice husk ash - Copoglu, Nurullah; Gokdemir, Hatice; Cengiz, Tamer; Cicek, Bugra (ELSEVIER SCI LTD, 2022)
The purpose of this study is the recycling or reuse of rice husk ash (RHA) in the production of silicate-based glass coatings for metal surfaces. RHA particles are heat-treated at 600 degrees C, 800 degrees C, 1000 degrees C, and 1200 degrees C temperatures for 2 h and analysed via XRF, XRD, FTIR, and SEM. Highest percentage of SiO2 ratio in the chemical composition is selected for further assessment by increasing the heat treatment duration. The SiO2 source in the batch of barium borosilicate glass coatings is taken from i) the calcined RHA with the greatest SiO2 ratio and ii) the as received RHA. The batch is melted at 1200 degrees C for 30 min and quenched. The resulting cullets are coated on a steel surface and the devitrification procedure is conducted at 810 degrees C for 4 min. Coatings were subjected to XRF, XRD, FTIR, SEM, DTA, and Heat Microscopy analyses and findings indicated the calcination procedure is required for amorphous coatings to preserve their technical characteristics. The residual tridymite phase arises because the cristobalite-tridymite transition during calcination does not occur in samples without calcination. It is proven that RHA can be used instead of silica, which is the basic material for silicate structures in borosilicate glass coatings.
Keywords: RHA; Glass; Coating; Barium borosilicate; Sustainability; TEMPERATURE; STABILITY; BEHAVIOR; QUARTZ; Materials Science